2007
DOI: 10.1103/physrevd.75.081501
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic glider

Abstract: We present a purely relativistic effect according to which asymmetric oscillations of a quasi-rigid body slow down or accelerate its fall in a gravitational background.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(57 citation statements)
references
References 4 publications
4
53
0
Order By: Relevance
“…The initial conditions are φ i (t = 0) =φ i (t = 0) = 0, r(t = 0) = r 0 andṙ(t = 0) = v 0 . The case with v 0 = 0 was discussed by Guéron and Mosna (2007). In that case, it is possible to slow down or to accelerate the free fall of a system depending on the parameter α. Guéron showed that after one oscillation period, the radial deviation is given by…”
Section: Radial Free Fallmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial conditions are φ i (t = 0) =φ i (t = 0) = 0, r(t = 0) = r 0 andṙ(t = 0) = v 0 . The case with v 0 = 0 was discussed by Guéron and Mosna (2007). In that case, it is possible to slow down or to accelerate the free fall of a system depending on the parameter α. Guéron showed that after one oscillation period, the radial deviation is given by…”
Section: Radial Free Fallmentioning
confidence: 99%
“…This situation is studied in Guéron and Mosna (2007), Bergamin et al (2009a). The initial conditions are φ i (t = 0) =φ i (t = 0) = 0, r(t = 0) = r 0 andṙ(t = 0) = v 0 .…”
Section: Radial Free Fallmentioning
confidence: 99%
See 3 more Smart Citations